Properties of TiBN coating on the tool steels by PECVD and its applications - Son, Myung Jin; Kang, Sung Soo; Lee, Eung-Ahn; Kim, Kwang Ho (Journal of materials processing technology, 2002)
During the warm and hot forging process of steels or aluminum alloys, dies are subject to early fracture and severe wear with the mechanical and thermal shocks. In this work, TiBN hard layer was successfully coated on SKD 61 steel substrate by a plasma-enhanced chemical vapor deposition (PECVD) technique, and field test was performed for the punch coated with it. The TiBN coating layer was found to be a composite consisting of TiN, TiB, and TiB 2 crystallites, and showed a superior hardness value up to 55 GPa by a nanoindentation method and good corrosion resistance. The punch for production of rotor pole, which was coated with TiBN hard coating layer, showed excellent performance and much increased service life compared with the conventional ones. The superior mechanical properties and corrosion resistance of TiBN coating layer reasoned for the much increased service life of coated punch.